Effect of high frequency repetitive transcranial magnetic stimulation on reaction time, clinical features and cognitive functions in patients with Parkinson's disease - Sedlácková, Silvie; Rektorová, Irena; Srovnalová, Hana; Rektor, Ivan (Journal of neural transmission (Vienna, Austria, 2009)
The aim of the present study was to investigate the effects of one session of high-frequency repetitive transcranial magnetic stimulation (rTMS) applied over the left dorsal premotor cortex (PMd) and left dorsolateral prefrontal cortex (DLPFC) on choice reaction time in a noise-compatibility task, and cognitive functions in patients with Parkinson's disease (PD). Clinical motor symptoms of PD were assessed as well. Ten patients with PD entered a randomized, placebo-controlled study with a crossover design. Each patient received 10 Hz stimulation over the left PMd and DLPFC (active stimulation sites) and the occipital cortex (OCC; a control stimulation site) in the OFF motor state, i.e. at least after 12 h of dopaminergic drugs withdrawal. Frameless stereotaxy was used to target the optimal position of the coil. For the evaluation of reaction time, we used a noise-compatibility paradigm. A short battery of neuropsychological tests was performed to evaluate executive functions, working memory, and psychomotor speed. Clinical assessment included a clinical motor evaluation using part III of the Unified Parkinson's Disease Rating Scale. Statistical analysis revealed no significant effect of rTMS applied over the left PMd and/or DLPFC in patients with PD in any of the measured parameters. In this study, we did not observe any effect of one session of high frequency rTMS applied over the left PMd and/or DLPFC on choice reaction time in a noise-compatibility task, cognitive functions, or motor features in patients with PD. rTMS applied over all three stimulated areas was well tolerated and safe in terms of the cognitive and motor effects.
Keywords: Cognition Disorders; reakční čas; mozková kůra; senioři; Cerebral Cortex; Aged; Male; biofyzika; transkraniální magnetická stimulace; Choice Behavior; lidé; Analysis of Variance; lidé středního věku; Humans; Biophysics; Parkinson Disease; Middle Aged; Electric Stimulation; krátkodobá paměť; Reaction Time; Transcranial Magnetic Stimulation; Psychomotor Performance; neuropsychologické testy; Memory, Short-Term; mužské pohlaví; analýza rozptylu; kognitivní poruchy; výběrové chování; Attention; ženské pohlaví; Parkinsonova nemoc; Neuropsychological Tests; Female; psychomotorický výkon; elektrická stimulace; pozornost